The Serial Mediation of Self-Efficacy and Learning Motivation on the Relationship Between Social Support and Arabic Language Proficiency - Ahmad Faiz Shaleh; M. Abdul Hamid; Danial Hilmi (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2026)
This study investigates the sequential psychological mechanisms underlying the relationship between social support and Arabic language proficiency. The aims of this study are: To examine the effect of social support on Arabic language proficiency through the sequential mediation of self-efficacy and learning motivation among students at State Islamic Universities in East Java. This research adopted a quantitative approach using a survey method. The research sample consisted of 200 respondents from Arabic Language Education Department students across four State Islamic Universities in East Java. The data were gathered through questionnaires and language proficiency tests. The data analysis technique utilized was Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings of this study indicate The serial mediation role was confirmed by the indirect effect of social support on Arabic language proficiency through the serial mediation of self-efficacy and learning motivation. The study demonstrates that students who received social support experienced an increase in their regarding self-efficacy. This self-efficacy, in turn, drove them to persist in their Arabic language studies, ultimately leading to their excellence in Arabic language proficiency. The Success in Arabic language education depends on an integrated system that begins socially, evolves cognitively, and culminates linguistically.